Analgesic ingestion and other factors preceding relapse in ulcerative colitis. Issue 3 (March 1983) - Rampton, D S; McNeil, N I; Sarner, M
Abstract : To investigate factors which predispose to relapse in patients with ulcerative colitis, we conducted a survey to compare the events occurring in the four weeks preceding the clinic attendance of 62 outpatients in remission with those taking place in the same period before the onset of relapse in 21 patients attending with active disease. The only event which occurred significantly more often in patients who subsequently relapsed was ingestion of paracetamol and other inhibitors of prostaglandin synthesis (76% (16/21) relapse vs 39% (24/62) remission, p less than 0 . 01). Recent upper respiratory tract infection (38% vs 26%) was not significantly more common in patients in relapse than in remission, and emotional stress, atopic events, antibiotic treatment, dietary indiscretions, foreign travel, and gastroenteritis were relatively rare in both groups. The surprisingly high prevalence of analgesic ingestion before relapse itself requires confirmation but does lend indirect support to the theory that colonic mucosal prostaglandin deficiency induces relapse in some patients with ulcerative colitis.